The good practices manifesto: Overcoming bad practices pervasive in current research in business - Woodside, Arch (Elsevier, 2016)
Under the “Metrics” link, Google.com/scholar ranks the top twenty journals by impact in 16 subcategories of “business, economics, and management” (e.g., accounting and taxation, economics, finance, marketing, strategic management, tourism and hospitality). This editorial describes bad practices appearing in the majority of published articles in the twenty leading journals within all of these 16 subcategories. Unfortunately, bad practices appear in most articles in the Journal of Business Research—even though the JBR is first in marketing and seventh in strategic management in the Google journal h5 impact rankings. Most of the articles in most of the journals in finance, management, marketing, and organizational studies include empirical positivistic methods and findings—and each of these empirical articles likely includes three-to-ten or more bad practices that this editorial describes. The editorial includes how to design-in good practices in theory, data collection procedures, analysis, and interpretations to avoid these bad practices. Given that bad practices in research are ingrained in the career training of scholars in sub-disciplines of business/management (e.g., through reading articles exhibiting bad practices usually without discussions of the severe weaknesses in these studies and by research courses stressing the use of regression analysis and structural equation modeling), this editorial is likely to have little impact. However, scholars and executives supporting good practices should not lose hope. The relevant literature includes a few brilliant contributions that can serve as beacons for eliminating the current pervasive bad practices and for performing highly competent research.